Ancaman Penyakit Hewan Menular Terhadap Ketahanan Nasional: Tantangan dan Strategi Mitigasi - Susanti, Eni; Hafid, Abdul; Sajidin, Muhammad; Mausili, Dwi Rianisa; Cahyani, Annisa Putri; Kurnia, Dihan; Nurhayati, Dwi; Sukoco, Hendro (Jayapangus Press, 2025)
Infectious animal diseases are increasingly exhibiting complex and transboundary patterns of spread, potentially disrupting food security, the economy, and public health. This study aims to identify and analyze the potential threats of infectious animal diseases to national resilience. The method used is a descriptive qualitative literature study through a review of scientific literature, policy documents, and reports from national and international institutions to map the relationship between the dynamics of infectious animal diseases and the pillars of national resilience. The results show that disease outbreaks such as foot-and-mouth disease, avian influenza, rabies, and tuberculosis have a significant impact on livestock productivity, the food supply chain, community social behavior, and the burden on the health system. Significant economic losses, increased zoonotic risks, and disruptions to socio-economic stability demonstrate that infectious animal diseases pose a multidimensional threat to food security, economic security, social security, and national security. These findings emphasize the need for a One Health-based mitigation strategy through strengthening integrated surveillance, increasing laboratory capacity, implementing biosecurity, adapting outbreak responses, and optimizing vaccination. This study contributes to strengthening national resilience policies by emphasizing the importance of cross-sectoral coordination in preventing and controlling infectious animal diseases as part of national biosecurity and stability.